An Interrupted Pummerer/Nickel‐Catalysed Cross‐Coupling Sequence. (5th July 2018) - Aukland, Miles H.; Talbot, Fabien J. T.; Fernández‐Salas, José A.; Ball, Matthew; Pulis, Alexander P.; Procter, David J.
Abstract: An interrupted Pummerer/nickel‐catalysed cross‐coupling strategy has been developed and used in the elaboration of styrenes. The operationally simple method can be carried out as a one‐pot process, involves the direct formation of stable alkenyl sulfonium salt intermediates, utilises a commercially available sulfoxide, catalyst, and ligand, operates at ambient temperature, accommodates sp‐, sp 2 ‐, and sp 3 ‐hybridised organozinc coupling partners, and delivers functionalised styrene products in high yields over two steps. An interrupted Pummerer/cyclisation approach has also been used to access carbo‐ and heterocyclic alkenyl sulfonium salts for cross‐coupling.